Rapid Review of Medication Taking (Adherence) Among Patients With Rheumatic Diseases During the COVID‐19 Pandemic. Issue 12 (22nd August 2022) - Rebić, Nevena; Park, Jamie Y.; Garg, Ria; Ellis, Ursula; Kelly, Ayano; Davidson, Eileen; De Vera, Mary A.
Abstract : Objective: We aimed to identify, appraise, synthesize, and contextualize rapidly emerging reports on medication taking (adherence) among patients with rheumatic diseases during the COVID‐19 pandemic. Methods: We searched MEDLINE, EMBASE, and CINAHL for peer‐reviewed communications, letters, and articles published during the COVID‐19 pandemic evaluating medication taking among individuals with rheumatic diseases. We appraised assessment and reporting of medication adherence according to established definitions of 3 distinct problems of medication taking (i.e., noninitiation, poor implementation, and discontinuation) and pooled findings using random‐effects models. Results: We included 31 peer‐reviewed studies in our synthesis from various jurisdictions, of which 25 described medication taking among rheumatology patients and 6 described medication prescribing among rheumatology providers. The pooled prevalence of overall medication nonadherence was 14.8% (95% confidence interval [95% CI] 12.3–17.2) and that of medication discontinuation (i.e., stopping of prescriptions) and poor implementation (i.e., not taking medication at the dose/frequency prescribed) as 9.5% (95% CI 5.1–14.0) and 9.6% (95% CI 6.2–13.0), respectively. Noninitiation (i.e., not starting/not filling new prescriptions) was not addressed. Conclusion: Medication taking among individuals with rheumatic diseases during the COVID‐19 pandemic varies globally. Unclear reporting and extensive variation in research methods between studies create barriers to research replication, comparison, and generalization to specific patient populations. Future research in this area should use consistent and transparent approaches to defining and measuring medication taking problems to ensure that findings appropriately describe the epidemiology of medication adherence and have the potential to identify modifiable targets for improving patient care.